Advanced visual interfaces : supporting big data applications : AVI 2016 Workshop, AVI-BDA 2016, Bari, Italy, June 7-10, 2016, Revised selected papers /: supporting big data applications : AVI 2016 Workshop, AVI-BDA 2016, Bari, Italy, June 7-10, 2016, Revised selected papers. (2016) - Unknown
No abstract available